Risk Factors for Autism Spectrum Disorder in Individuals Born Preterm: A Systematic Review and Meta-Analysis of Population-Based Studies - Bo Yang; Nina Zaks; Eero Kajantie; Monica S.M. Persson; Abraham Reichenberg; Mika Gissler; Kari Risnes; Alexander Kolevzon; Ulrika Ådén; Ezra Susser; Martina Persson; Jonas F. Ludvigsson; et al. (Biological Psychiatry Global Open Science, 2025)
Background: Preterm children are at an increased risk of autism spectrum disorder (ASD), although the determinants of ASD among them remain unclear. In this systematic review and meta-analysis, we summarize the population-based literature on ASD risk factors in preterm-born individuals. Methods: We searched Ovid MEDLINE, Embase, and Web of Science through September 2023 for population-based studies on ASD risk factors in preterm cohorts (<37 weeks’ gestation). From 3921 articles, 19 met inclusion criteria. Registered in PROSPERO and following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, data were extracted and analyzed using fixed and random effects meta-analysis models. Primary outcomes included ASD risk factors, pooled when consistently examined in at least 2 studies. Results: The qualitative synthesis included 16 cohort studies, 2 case-control studies, and 1 cross-sectional study, while 3 cohort studies were included in the meta-analysis. Sample sizes ranged from 410 to 515,789. Male sex was the only risk factor eligible for meta-analysis and was associated with increased risk of ASD (relative risk 3.04; 95% CI, 2.02–4.57). Low birth weight suggested a potential positive association with ASD, while neonatal jaundice showed no clear link. Pooled estimates were unavailable for these exposures due to heterogeneity in exposure definitions and effect measures. All other risk factors were examined in two or fewer studies. Conclusions: Significant knowledge gaps remain regarding the risk of ASD in individuals born preterm. The only consistent risk factor identified is male sex, with potential links to low birth weight. To better understand the differences in ASD etiology between preterm and term-born individuals, further research is crucial.